2008
DOI: 10.1677/jme-07-0133
|View full text |Cite
|
Sign up to set email alerts
|

CaV1.2 rather than CaV1.3 is coupled to glucose-stimulated insulin secretion in INS-1 832/13 cells

Abstract: In clonal b-cell lines and islets from different species, a variety of calcium channels are coupled to glucose-stimulated insulin secretion. The aim of this study was to identify the voltage-gated calcium channels that control insulin secretion in insulinoma (INS)-1 832/13 cells. The mRNA level of Ca V 1.2 exceeded that of Ca V 1.3 and Ca V 2.3 two-fold. Insulin secretion, which rose tenfold in response to 16 . 7 mM glucose, was completely abolished by 5 mM isradipine that blocks Ca V 1.2 and Ca V 1.3. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…The L-type α1C subunit expression exceeded that of α1D 10-fold in INS-1 cells, but only 2-fold in the β cells. These results were similar to recent research in INS-1 832/12 cells which confirmed that α1C subunit expression exceeded that of the α1D subunit by twofold and that the α1C subunit had a critical role in insulin secretion [18] . The L-type α1C subunit performs a special function in the first phase of insulin secretion and glucose tolerance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The L-type α1C subunit expression exceeded that of α1D 10-fold in INS-1 cells, but only 2-fold in the β cells. These results were similar to recent research in INS-1 832/12 cells which confirmed that α1C subunit expression exceeded that of the α1D subunit by twofold and that the α1C subunit had a critical role in insulin secretion [18] . The L-type α1C subunit performs a special function in the first phase of insulin secretion and glucose tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, L-type α1C subunits were dominant among all subunit expressions, which was in accordance with its important biological function in both INS-1 and rat β cells. The L-type α1D subunit's roles in insulin secretion or proliferation were not confirmed until recently [18,[20][21][22] . The expression of the non-voltage-operated Ca 2+ channel subunits Ryr2, TRPC1, TRPC4α, TRPC4β, and IP3R1 in rat β cells exceeded those in INS-1 by 10-fold and TRPM2 expression was not significantly different between the β cells and INS-1.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that Ca v 1.3 knockdown reduced insulin release in INS-1 832/13 cells. A previous study suggested that Ca v 1.2 knockdown diminished GSIS [46] but as we did not test siRNA against Ca v 1.2, it may well be that both channels are crucial for appropriate insulin release in these cells.…”
Section: Discussionmentioning
confidence: 75%
“…However, neither expression of critical calcium channels nor insulin content is different in the two subclones (11). Furthermore, Newgard and co-workers (13) showed that glucose responsiveness in different INS-1 subclones correlates with an increased flux in an anaplerotic pathway, termed pyruvate cycling.…”
Section: Discussionmentioning
confidence: 99%
“…The 832/2 and 832/13 subclones express similar levels of Ca(V)1.2, Ca(V)1.3, and Ca(V)2.3 Ca 2ϩ channels, which are involved in GSIS in ␤-cells. This suggests that altered calcium channel activity is not responsible for discrepant insulin secretion responses (11). Furthermore, these clones are characterized by similar insulin content (12).…”
mentioning
confidence: 91%